Tubulointerstitial Nephritis and Uveitis (TINU) Syndrome: a systematic review - Joana Filipa Magalhães Pereira (2022)
Background: Tubulointerstitial nephritis and uveitis (TINU) syndrome is a rare disease characterized by the occurrence of tubulointerstitial nephritis (TIN) and uveitis, in the absence of other explainable systemic disease. In this review we aim to appraise and to clarify what is acknowledged in order to elucidate the demographics, genetic predisposition, most frequent symptoms and laboratory findings, most adequate treatment and also patient's prognosis. Methods: A systematic review across PubMed, ISI Web of Knowledge and SCOPUS was performed, according to PRISMA guidelines, in order to identify all relevant articles regarding both tubulointerstitial nephritis and uveitis. Results: We identified 240 publications, of which 176 were excluded. The average age of TINU syndrome diagnosis was 30.6 years-old, with a female predominance (2:1); according to presentation symptoms, TIN precedes uveitis more commonly and amongst uveitis cases the majority were bilateral anterior uveitis. Moreover, the most common systemic symptoms were fatigue, fever, and weight loss; blood analysis commonly presented with elevated serum creatinine (sCr), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), blood urea nitrogen level (BUN) and urinalysis frequently showed proteinuria, glycosuria, and elevated urinary-2-microglobulin. The majority (78.8%) of patients were putted on corticosteroids, with 21.9% needing an additional immunosuppressor, being mycophenolate mofetil (29.8%) and azathioprine (28.0%) the preferred ones. The mean time until relapse, which occurred in 48.3% of patients, was 89.3 days. Conclusion: TINU is not just a pediatric syndrome, as once thought. Presentation seems to be variable, although TIN typically presents first, with systemic symptoms such as fatigue. As clinicians becomes more aware of the disease, follow-up after the first symptoms allows for earlier diagnosis. Relatively to treatment, most patients responded to corticosteroids, and despite the relapses, the prognosis was generally favorable.